A review of the Obras por Impuestos regulation regarding dispute resolution and Dispute Boards - Benavente, Carlos Tapia (2023)
This article will analyze the current regulation of the mechanism of Obras por Impuestos, specifically, the tools for dispute resolution and will evaluate the possibility of including Dispute Boards as a contribution to prevent and solve disputes in a timely manner, cost efficient, and to promote the use of Obras por Impuestos to reduce the infrastructure gap in Peru.